Peranan Insentif Dalam Meningkatkan Produktivitas Kerja Pegawai Di Rumah Tahanan Negara Kelas IIB Sukadana - Suryadi, Suryadi; Dupri, Muhammad Demsi; Hardianti, Indri (Universitas Muhammadiyah Metro, 2023)
Work productivity in the sense that companies or agencies can directly see their workforce toproduce a number of units of goods measured based on units of time, so the purpose of thisresearch is to determine the role of incentives in increasing employee productivity at theSukadana Class IIB State Detention Center. This type of research is quantitative. Thedescription of this research is partially that the variables studied with a population of 51employees and found a sample of 45 employees the sampling technique used is purposivesampling. The steps are carried out by distributing questionnaires and assisted by dataanalysis through validity, reliability, and simple regression tests. The conclusion of thisresearch is that incentives have a good role in increasing employee work productivity andachieving the goals expected by agencies/organizations at the Class IIB Sukadana StateDetention Center, East Lampung.